Identification of a Novel ASAH1 Gene Mutation in Spinal Muscular Atrophy with Progressive Myoclonic Epilepsy: Novel ASAH1 Gene Mutation in SMA-PME - Ahangari, Najmeh; Arab, Fatemeh; Babaei, Meisam (Iranian Journal of Child Neurology, 2024)
Spinal muscular atrophy (SMA) with progressive myoclonic epilepsy (PME) affects the nervous system. Symptoms appear in early childhood and include muscle weakness, difficulty walking, seizures, and cognitive decline. Despite introducing various therapies to restore acid ceramidase function or reduce ceramide accumulation and gene therapy to correct genetic mutations, there are still unknown underlying molecular mechanisms related to this disorder. This article reports a novel variant c.118G>C in the ASAH1 gene. The patient presented with clinical manifestations such as progressive muscle weakness and myoclonic convulsions. Clinical features and electrophysiological investigations revealed a motor neuron disease and generalized epileptic discharge. A significant temporal interval was observed between the initial diagnosis of SMA and the subsequent manifestation of myoclonic seizures. The proband was genetically assessed through whole exome sequencing (WES) followed by variant confirmation and bioinformatics analysis. According to this article’s findings and previous research, further diagnostic testing and management are needed to determine the severity and progression of the patient’s condition